2021
DOI: 10.3390/f12070902
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Biomass Estimation in Short Rotation Forest Plantations in Northern Greece Using ESA’s Sentinel Medium-High Resolution Multispectral and Radar Imaging Missions

Abstract: Plantations of fast-growing forest species such as black locust (Robinia Pseudoacacia) can contribute to energy transformation, mitigate industrial pollution, and restore degraded, marginal land. In this study, the synergistic use of Sentinel-2 and Sentinel-1 time series data is explored for modeling aboveground biomass (AGB) in black locust short-rotation plantations in northeastern Greece. Optimal modeling dates and EO sensor data are also identified through the analysis. Random forest (RF) models were origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…The clone with the best height growth, 'NK2', produced 10% of its height increment between September and November, despite the fact, that during the growing season droughty periods occurred, which caused water shortage problems on the sandy soil. Similar to the results of Theofanous et al [81], the maximum values of height increments for the clones studied coincided with the NDVI values.…”
Section: Discussionsupporting
confidence: 90%
“…The clone with the best height growth, 'NK2', produced 10% of its height increment between September and November, despite the fact, that during the growing season droughty periods occurred, which caused water shortage problems on the sandy soil. Similar to the results of Theofanous et al [81], the maximum values of height increments for the clones studied coincided with the NDVI values.…”
Section: Discussionsupporting
confidence: 90%
“…For samples smaller than 5 cm or rotten ones in decay class 5, only one horizontal measurement was taken by a caliper. The woody debris volume was estimated using the formula of the truncated cone and for the conversion of volume into dry biomass, the wood density reduction according to decay classes [30] was used.…”
Section: Inventory Datamentioning
confidence: 99%
“…AGB estimation over a domain is based on a combination of ground reference measurements such as classical field-data (forest inventory data) and the harvest of selected trees that are subsequently oven-dried and weighed for deriving accurate estimation of above ground biomass [28,29]. In some cases, however, auxiliary variables derived from satellite-based products (including LIght Detection And Ranging (LIDAR) technology) are used to render more precise spatial estimation of AGB over the desired domain [30][31][32]. Ground reference measurements can provide accurate estimates for the calibration and validation of global satellite-based AGB models.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the fusion of SAR with optical sensor data improves AGB estimation, as optical data offset the saturation impact. Therefore, AGB monitoring has improved as a result of the latest developments in satellite systems [236][237][238][239]. However, the SAR works for a particular range of AGB, and beyond this range, the system provides coarse data [240].…”
Section: Agbmentioning
confidence: 99%